Pens for Hire: Part 3 - Buerger, Geoffrey E. (Canadian Perspectives on Academic Integrity, 2023)
This is Part 3 of a three part invited article series examining the historical evolution of the contract cheating industry. Parts 1 and 2 were concerned chiefly with the emergence of the commercial trade in academic work in the United States and the varied responses it elicited in that country. This article discusses Canadian attempts to combat that phenomenon, and focusses on York University’s actions against Custom Essay Service in the late 1980s. Part 3 concludes with a series of questions to encourage reflection and discussion with students or educators and practitioners.